Stem and leaf hydraulic properties are finely coordinated in three tropical rain forest tree species. (14th July 2015) - Nolf, Markus; Creek, Danielle; Duursma, Remko; Holtum, Joseph; Mayr, Stefan; Choat, Brendan
Abstract: Coordination of stem and leaf hydraulic traits allows terrestrial plants to maintain safe water status under limited water supply. Tropical rain forests, one of the world's most productive biomes, are vulnerable to drought and potentially threatened by increased aridity due to global climate change. However, the relationship of stem and leaf traits within the plant hydraulic continuum remains understudied, particularly in tropical species. We studied within‐plant hydraulic coordination between stems and leaves in three tropical lowland rain forest tree species by analyses of hydraulic vulnerability [hydraulic methods and ultrasonic emission (UE) analysis], pressure‐volume relations and in situ pre‐dawn and midday water potentials ( Ψ ). We found finely coordinated stem and leaf hydraulic features, with a strategy of sacrificing leaves in favour of stems. Fifty percent of hydraulic conductivity (P50 ) was lost at −2.1 to −3.1 MPa in stems and at −1.7 to −2.2 MPa in leaves. UE analysis corresponded to hydraulic measurements. Safety margins (leaf P50 – stem P50 ) were very narrow at −0.4 to −1.4 MPa. Pressure‐volume analysis and in situ Ψ indicated safe water status in stems but risk of hydraulic failure in leaves. Our study shows that stem and leaf hydraulics were finely tuned to avoid embolism formation in the xylem. Abstract : Coordination of stem and leaf hydraulic traits allows terrestrial plants to maintain safe water status under limited water supply, but the relationship of such traits within the plant hydraulic continuum remains largely understudied. In this study we analysed the hydraulic vulnerability, pressure‐volume relations and in situ water potentials of three tropical rainforest species. We found that hydraulic parameters in stems and leaves were finely coordinated to avoid embolism formation in the xylem, with very narrow safety margins (leaf P50 – stem P50 ) and a strategy of sacrificing leaves in favour of stems.